Vous êtes sur la page 1sur 9

Y Waves & Sound Waves

φ A
x X
-A

Equation of a progressive wave :

Wave is defined as a propagating particle executing SHM.

The equation of a propagating SHM particle is : Y = A sin (ωt ± φ)

Where, A is the amplitude of oscillation, ω is the angular velocity of the particle executing SHM = 2πn, φ is the initial
phase difference of the particle when t = 0 (known as epoch)

Now, when the path difference of the particle is λ, corresponding phase difference is 2π. Clearly, if the path difference is
x, corresponding phase difference will be, φ = (2π/ λ)x = 2πx/ λ, where k = 2π/ λ, known as wave constant. So φ = kx

So, the equation of a progressive wave can be written in the following ways :
 Y = A sin (ωt ± φ)
 Y = A sin (ωt ± kx) [Where, k = 2π/ λ, known as wave constant]
 Y = A sin (2πt/T ± 2πx/ λ) [ where, ω = 2π/ T]
 Y = A sin 2π (t/T ± x/ λ)
 Y = A sin 2π (nt ± x/ λ) [ where, n = 1/T, known as the frequency of the wave]

Differential equation of a progressive wave (1 dimensional) :

Now, the general equation of a progressive wave can be written as :


Y = A sin (ωt + kx) ---(i) [ where, the displacement of the particle at any instant t is along Y direction,
depends on the propagation time t and the initial path difference x. and
A, ω = 2π/T, k = 2π/ λ are constants.]

Differentiating equation (i), with respect to t, we get


Particle velocity, V = dY/dt = Aω cos (ωt + kx)
And, particle acceleration, a = d2Y/dt2 = - Aω2 sin (ωt + kx) = - ω2Y ----------------------------(ii)

Differentiating equation (i), with respect to x, we get

dY/dx = Ak cos (ωt + kx)


d2Y/dx2 = - Ak2 sin (ωt + kx) = - k2Y ---------------------------------(iii)

Dividing equation (ii) by (iii), we get :

d2Y/dt2 = - ω2Y
d2Y/dx2 - k2Y
 d Y/dt2 = (ω/k)2 d2Y/dx2
2

 d2Y/dt2 = v2 d2Y/dx2 -------------(iv) [ where, ω/k = (2π/T)/(2π/λ) = λ/T = nλ = v, velocity of the wave]
Equation (iv) is known as the differential equation of a progressive I dimensional wave.
v = nλ, known as the wave velocity

 Difference between particle velocity and wave velocity :

Particle velocity, V = dY/dt = Aω cos (ωt + kx), is the velocity of the wave particle by which it vibrates at any
instant t. It’s magnitude depends upon time, its maximum magnitude is Aω.

Whereas wave velocity v = nλ, is the velocity of the whole wave (disturbance). Its magnitude depends upon the
frequency and the wavelength of the wave, It remains constant throughout the motion.

 Superposition of two waves :

1. Same amplitude (A1 = A2 = A) but different angular frequencies (ω1 ≠ ω2)

Let us consider two waves Y1 = A sin ω1t and Y1 = A sin ω2t are superimposed over each other.
We get, Y = Y1 + Y2 = A (sin ω1t + sin ω2t)
 Y = 2A [cos (ω1 - ω2)/2]sin (ω1 + ω2)/2
 Y = A/ sin ωt, So, the resultant wave also having same frequency ω = 2πn as the superposing wave.
But the amplitude is changed.
Where, A/ = 2A [cos (ω1 - ω2)/2]
If, ω1 - ω2 = 0
 2πn1 - 2πn1 = 0
 n1 = n2, i.e. both the waves are superimposed with same frequency, the resultant waves amplitude A/ = 2A, known
as resonating condition.
And Δn = n1 – n2 is known as the number of beats.

2. Different amplitudes (A1 ≠ A2) but same angular frequencies (ω1 = ω2 = ω)

Let us consider two monochromatic waves Y1 = A1 sin wt and Y2 = A2 sin (wt-θ) are superimposed over
each other. The resultant wave will be
Y = Y1 + Y2 = A1 sin wt + A2 sin (wt-θ)
 Y = A1 sin wt + A2 sin wt cos θ – A2 cos wt sin θ
 Y = sin wt (A1 + A2 cos θ) - A2 cos wt sin θ
 Y = A sin wt cos α – A cos wt sin α [ Where A cos α = (A1 + A2 cos θ) and A sin α = A2 sin θ]
 Y = A (sin wt cos α – cos wt sin α)
 Y = A sin (wt – α)
So, after superposition, it is found that, the nature of the wave remains simple harmonic in nature with
same angular speed w but the amplitude A and the phase difference α of the resultant wave is changed.

Now, A cos α = (A1 + A2 cos θ)


=> A2 cos 2 α = A12 + A22 cos2θ + 2 A1A2 cos θ --------------(v) [ Squaring both sides]
And, A sin α = A2 sin θ
=> A2 sin2 α = A22 sin2 θ --------------------(vi)
Adding (i) and (ii), we get,
A2 (sin2 α + cos 2 α) = A12 + A22 cos2θ + 2 A1A2 cos θ + A22 sin2 θ
 A2 = A12 + A22 (sin2 θ + cos 2 θ) + 2 A1A2 cos θ
 A2 = A12 + A22 + 2 A1A2 cos θ -----------------------(vii)

Since, Intensity (I) ∞ Amplitude2 (A2), so equation (v) can be rewritten as :


I = I1 + I2 + 2 √I1I2 cos θ ---------------------------------(viii)

 Condition for Interference Maxima:

Now, when the phase difference between the two waves, θ = 0, => cos θ = 1, i.e. both waves are
superposing at the same phase
We get, Amax = A1 + A2 and Imax = (√I1 + √I2)2 -----------------------(ix)
Known as constructive interference pattern.

General condition :
cos θ = 1 => θmax = 2nπ [Condition for Interference Maxima] -----------------------(x)

 Condition for Interference Minima:

And, when the phase difference between the two waves, θ = π, => cos θ = -1, i.e. both waves are
superposing in the opposite phase
We get, Amin = A1 - A2 and Imin = (√I1 - √I2)2 -------------------------------(xi)
Known as destructive interference pattern.

General condition :
cos θ = -1 => θmin = (2n + 1)π = (n + ½)2π [Condition for Interference Minima] -------------------(xii)

Silent Zone : When a sound wave originated from a source is superimposed over its reflected
component, a phase difference of π is produced between the incident and the reflected wave with the
same amplitude (A1 = A2 = A). So following the conditions of destructive interference pattern of sound
waves the resultant amplitude Amin = A – A = 0, becomes zero, Thus the intensity of the sound wave at
that region also becomes zero. Thus no sound wave is produced at that zone, known as silent zone or
silent place. Silent Zone
3. Same amplitude ( A1 = A2 = A ), same angular frequencies (ω1 = ω2 = ω)

Let us consider two waves Y1 = A sin (kx + ωt) and Y2 = A sin (kx – ωt) are superimposed from the opposite
directions [ Actually, one wave is reflected, that’s why a phase difference of π is produced ] Under this condition,
the resultant wave will have zero velocity, but the particles will continue oscillatory motion.

After superposition, we get, Y = Y = Y1 + Y2 = A [sin (kx + ωt) + sin (kx - ωt)]


 Y = [2Acos ωt] sin kx
 Y = A/ sin kx, which is a time independent wave is known as stationary wave, where the amplitude A / = 2A
becomes maximum when cos ωt = 1 i.e. ωt = 2nπ => t = nT [ n = 1,2,3 …]

v -v

 Stationary waves (Standing waves) :

Let us consider two waves Y1 = A sin (φ + ω1t) and Y1 = A sin (φ - ω2t) are superimposed over each other
from opposite directions, the resultant waves would be :

ω1

Nodes nodes anti nodes nodes anti nodes nodes t

ω2

Y = A sin (φ + ω1t) + A sin (φ – ω2t)


 Y = A [sin (φ + ω1t) + sin (φ – ω2t)]
 Y = 2A sin φ cos (ω1 + ω2)t/2
 Y = 2A sin φ cos ωt
 Y = A/ cos ωt.
The wave velocity for the wave v = nλ = 0, known as the Stationary wave or standing wave. But its particle
velocity will not be zero at all the points. The points at which the particle amplitude is maximum are known as
Anti Nodes. And the points at which the amplitude of the particle is minimum are known as nodes.
Conditions for anti nodes :

When A/ = 2A = Amax, the anti nodes are formed.


i.e, sin φ = 1
 φ = (n + ½)π
 kx = (n + ½)π [ φ = kx ]
 2πx/λ = (n + ½)π [ where, 2π/λ= k ]
 x = (n + ½)λ/2, n = 0, 1, 2, ….
i.e anti nodes are produced at λ/4, 3λ/4, 5λ/4,…

Conditions for nodes :

When A/ = 0, the nodes are formed.


i.e, sin φ = 0
 φ = nπ
 kx = nπ [ φ = kx ]
 2πx/λ = nπ [ where, 2π/λ= k ]
 x = nλ/2, n = 0, 1, 2, ….
i.e nodes are produced at 0, λ/2, λ, ,…

Open Organ Pipes and Closed Organ Pipes :

Closed organ pipe:


For the first superposition : λ/4 = L
L λ/4 λ = 4L
Fundamental frequency n1 = V/ λ = V/4L
λ/4 For the 2 nd superposition in a closed organ pipe : λ/4 + λ/2 = L
3λ/4 = L
λ = 4L/3
L λ/2
n2 = V/ λ = 3V/4L

λ/4
λ/4 For 3 rd superposition in a closed organ pipe : λ/4 + λ = L
5λ/4 = L
λ = 4L/5
L n3 = V/ λ = 5V/4L
λ

So the ratio of frequencies in a closed organ pipe is : n1 : n2 : n3 : . . . = V/4L : 3V/4L : 5V/4L : . . . = 1 : 3 : 5 : …


So only the odd number of frequencies remain present in the music originated from a closed organ pipe.

Open Organ Pipes :

For the first superposition : λ/4 + λ/4 = L


λ/4 λ/2 = L
λ = 2L
L Fundamental frequency n1 = V/ λ = V/2L

λ/4

λ/4
λ/4 For the second super position : λ/4 + λ/2 + λ/4 = L
λ=L
λ/2 L λ
L n2 = V/λ = V/L = 2V/2L

For the 3 rd superposition :


λ/4 λ/4 + λ + λ/4 = L λ/4
3 λ/2 = L
λ = 2L/3
n3 = V/λ = 3V/2L

So the ratio of frequencies in a open organ pipe is : n1 : n2 : n3 : . . . = V/L : 2V/2L : 3V/2L : . . . = 1 : 2 : 3 : …


So all of the frequencies remain present in the music originated from a closed organ pipe. So, the sound produced by an
open organ pipe is more reach in frequencies (double reach) than a closed pipe.

Sound waves :

Velocity of the sound waves in different mediums :

a) For solid medium : VSolid = √(Y/ρ) [ where Y = Young’s modulus of the solid and ρ = density of the solid]
b) For Fluid : VFluid = √(K/ρ) [ where K = Bulk’s modulus of the liquid and ρ = density of the liquid]
c) For String ( 1 D Solid): VString = √(T/m) [ where T = Tension of the string and m = mass per unit length]
d) For Gas : Vgas = √(γP/ρ) [ where γ = ratio of specific heat capacities of the gas, P = Pressure of the gas, ρ =
density of the gas]

Velocity of sound wave in a string : When a string is pulled due to tension, a small loop is produced. In which tension
takes place along the tangential direction.
MV2/R

A T cosθ θ O θ T cosθ A/

T 2T sinθ T

The small tension generated over the loop of the wire is T. The horizontal components of tension T cosθ will
be mutually balanced and the vertically downward components from both sides 2T sin θ will give the
centripetal force.
So, 2T sin θ = MV2/R [ M is the mass of the length of the wire, R is the radius of the small loop,
V is the velocity of sound in the loop]
Since the angle θ is very small,
2Tθ = m dL V2/R [ M = m dL, m = mass per unit length of the wire, dL = lengthy of the small loop]
 T dL/R = m dL V2/R [ 2θ = dL/R]
 VString = √(T/m)

Velocity of Sound wave in gas :

Newton’s law : Newton considered that the velocity of sound wave through gaseous medium is an Isothermal process
(Temperature remain constant). So it should follow the equation
PV = RT = constant
 PdV + VdP = 0
 VdP = - PdV
 -VdP/dV = P
 K=P [ Bulk modulus K = dP/-(dV/V) = -VdP/dV]
 So velocity of sound wave in gases : Vgas = √(K/ρ) = √(P/ρ)
But this value did not tally with the experimental value of sound wave in the gas.
Laplace’s correction :
Laplace considered that velocity of sound wave in a gaseous medium is a very fast process and hence it is an
Adiabatic process (No heat exchange take place during this process)

So the gas equation it follows is,


PVγ = constant [ where, γ = CP/CV, the ratio of two specific heat capacities of gas]
 dPVγ + γPVγ-1dV = 0
 Vγ-1[VdP + γPdV] = 0
 VdP = - γPdV
 -VdP/dV = γP
 K = γP [Bulk modulus K = dP/-(dV/V) = -VdP/dV]
 So velocity of sound wave in gases : Vgas = √(K/ρ) = √(γP/ρ)
This value was almost equal to the experimental value.

 Sound wave also follow the same reflection formula like light waves.
 During refraction from the rarer surface (air) to the denser surface (e.g. water), since the velocity of sound
wave in air is more than water, (Vair > Vwater)
 sin i / sin r = Vair /Vwater > 1
 i > r ….i.e. sound wave bends away from the normal when it refracts from the rarer medium to the denser
medium. (opposite to the light wave)

Incident sound Normal Rarer medium

Air, VAir > VWater

r Refracted Sound

Water
DOPPLER EFFECT :
The change of the frequency of the sound due to the relative velocity between the source and the listener is known
as Doppler Effect. V = Velocity of sound, vS = velocity of source, vL = Velocity of the listener.

 Source at rest, Listener is moving towards the source :

V vL

Source vS = 0 Listener

The relative velocity of sound with respect to source : V – vS = V [ since vS = 0]


So the wave length generated is λ = V/n [ n = frequency of originated wave]
The relative velocity of sound with respect to Listener : V + vL
So the changed frequency to the listener will be :
n/ = (V + vL)/λ
 n/ = (V + vL)n/V = n(1 + vL/V)
i.e. the frequency will increase.

 Source moving towards the Listener and Listener is at rest :

vS
V

Source vS Listener

The relative velocity of sound with respect to source : V – vS


So the wave length generated is λ = (V – vS )/n [ n = frequency of originated wave]
The relative velocity of sound with respect to Listener : V + vL = V [As vL = 0]
So the changed frequency to the listener will be :
n/ = V/λ
 n/ = Vn/(V – vS)
i.e. the frequency will increase.

 Source moving towards the Listener and Listener is moving towards the source :

vS vL
V

Source Listener

The relative velocity of sound with respect to source : V – vS


So the wave length generated is λ = (V – vS )/n [ n = frequency of originated wave]
The relative velocity of sound with respect to Listener : V – vS + vL
So the changed frequency to the listener will be :
n/ = (V – vS + vL )/λ
 n/ = (V – vS + vL)n/(V – vS ) = [ 1+ vL/(V – vS )]n
i.e. the frequency will increase.